The influence of international mobility programmes on nursing students' personal and professional development - Igor Karnjuš; Mirko Prosen; Boško Krivičić; Sabina Ličen (Nurses and Midwives Association of Slovenia, 2020)
Introduction: Student mobility programmes have become a valuable instrument in student education as they enable the acquisition of essential knowledge, skills and attitudes, and equip the individual more effectively to work in the globalised world. The aim of the study was to examine the impact of international exchange programmes on the personal and professional development of undergraduate nursing students. Methods: A quantitative secondary analysis was conducted. The primary data were collected in 2016 as part of the study entitled International Nursing Student Exchange - Comparison Between Slovene and Foreign Students. The sample in the secondary analysis consisted of 73 nursing students from Slovenia and other European countries. The questionnaire included 20 statements which were rated on a 5-point Likert scale (1-strongly disagree to 5-strongly agree). The data were described on the basis of calculated mean values and the Mann-Whitney U test. Results: On the personal level, students stressed that mobility can improve their self-confidence (Z = -2.088, p = 0.037) and acceptance of other cultures (Z = -3.116, p = 0.002). On the professional level, they highlighted the need to upgrade students' professional competencies (Z = -3.116, p = 0.002), particularly in the field of culturally competent nursing care (Z = -2.391, p = 0.017). Discussion and conclusion: The benefits reported by nursing students seem to show that it is sensible to continue to support and promote international student mobility programmes.